Application of Problem-Based Learning Combined with Micro-Video Teaching in Burn Surgery and Its Impact on Satisfaction with Teaching - Zunjiang Zhao; Dalun Lv; Lei Chen (Journal of Investigative Surgery)
Objective This article aimed to ascertain the application of problem-based learning (PBL) combined with micro-video teaching in burn surgery teaching and its impact on satisfaction with teaching.Methods Fifty clinical medical students who were interns at our hospital from November 2022 to October 2023 were selected as the study subjects and randomly separated into the control group (n = 25) and the observation group (n = 25). The control group adopted traditional teaching methods. The observation group employed PBL combined with micro-video teaching mode. The scores of theory tests and skill tests, the critical thinking capability, the students’ evaluation of teaching methods, the scores of teachers for teaching methods, and the scores of interns for teaching satisfaction were compared.Results The observation group possessed higher scores on theory tests and skill tests, greater critical thinking ability after teaching, higher evaluation of teaching methods and more satisfaction with their internships versus the control group (all p < 0.05).Conclusion The application of PBL combined with micro-video teaching in the teaching of burn surgery can improve students’ thinking ability and their satisfaction with teaching.